Povidone Iodine as Sclerotherapy Into the Renal Pelvis for the Management of Chyluria: Our Experience (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the effectiveness and safety of 0.2% povidone iodine renal pelvic instillation as minimally invasive therapy for chyluria resistant to conservative treatment.Methods: From July 2015 to December 2016, 9 patients with chyluria were treated. There were 2 males and 7 females ranging from 30-65 years of age. Cystoscopic localization of chylous efflux was done. On a day care basis under local anesthesia a 5 Fr open ended ureteric catheter was introduced on the affected side. Freshly prepared 10 ml 0.2% Povidone iodine solution was instilled as a sclerosing agent in the renal pelvis. A total of 3 doses were given at 8-hour intervals. Unilateral instillation was done in 8 cases, and bilateral instillation was done in 1 patient.Result: Eight of 9 patients showed complete clearance. In 1 patient, recurrence was noted and a repeat injection was given after 4 weeks, with success.Conclusion: Our experience shows that povidone iodine is a safe and effective sclerosing agent in the management of chyluriaBangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.78-81